Synthesis of 2, 3‐Dihydro‐4‐pyridones, 4‐Quinolones, and 2, 3‐Dihydro‐4‐azocinones by Visible‐Light Photocatalytic Aerobic Dehydrogenation. Issue 10 (13th June 2019) - Sevenich, Adrian; Mark, Paulina Sophie; Behrendt, Torsten; Groß, Jonathan; Opatz, Till
Abstract : The synthesis of 2, 3‐dihydro‐4‐pyridones and 4‐quinolones was realized by visible‐light mediated photoredox‐catalyzed aerobic dehydrogenation of 4‐piperidones and 2, 3‐dihydro‐4‐quinolones. This method enables the synthesis of cyclic enaminones in up to 89 % yield under mild and eco‐friendly conditions and with a high tolerance of functional groups using oxygen as an inexpensive terminal oxidant and rhodamine 6G as a readily available organic photocatalyst. The process can be extended to access 2, 3‐dihydro‐4‐azocinones in up to 62 % yield via a [2+2] cycloaddition/ring‐expansion sequence in a telescoping one‐pot reaction. Hence, a protocol for the synthesis of three different types of N‐heterocycles was developed on the same general transformation. Abstract : A protocol for the synthesis of three types of N‐heterocycles was developed. Cyclic enaminones were prepared under eco‐friendly conditions by photocatalytic dehydrogenation using rhodamine 6G as inexpensive photocatalyst and oxygen as the terminal oxidant. The method was extended to access azocinones by a [2+2] cycloaddition/ring‐expansion sequence in a one‐pot procedure.